Використання та відтворення ресурсного потенціалу аграрного бізнесу за умов інклюзивної економіки - Степаненко, С. В. (My University, 2023)
Загострення глобальних проблем існування людства призвело до швидкої і кардинальної зміни ціннісних орієнтирів та стратегічних пріоритетів подальшого розвитку світових економік. На зміну і доповнення домінуючих комерційних концепцій управління бізнесом прийшли концепції соціально-екологічної та економічної справедливості, рівності та доступу до економічних благ. Однією з домінантних за таких реалій стала концепція інклюзивного розвитку, принципи якої спрямовані на подолання розривів і нерівностей у рівнях якості життя населення. Вирішальна роль при цьому відводиться аграрному сектору. У статті досліджено ключові пріоритети інклюзивного аграрного бізнесу, його характеристики та засади. Проведено огляд літературних джерел, присвячених питанню інклюзивності розвитку сільського господарства і сільських територій. У авторській варіації доповнено сукупність основних принципів інклюзивного аграрного бізнесу. Окреслено ландшафт основних завдань використання ресурсного потенціалу агробізнесу за умов інклюзивної аграрної економіки. Проведено аналіз стану, обсягів та вартості ресурсного потенціалу агробізнесу України за умов довоєнного часу. Результати досліджень показали наявність значних проблем формування ресурсного потенціалу агросфери у частині людських ресурсів, основних засобів та нематеріальних активів. Незважаючи на це, результати продемонстрували інвестиційну привабливість агросектору та високі показники рентабельності агробізнесу. Все це підтвердило тезу про наявність значного потенціалу забезпечення майбутнього економічного зростання галузі на засадах інклюзивного розвитку. Неодмінною передумовою реалізації даної мети має стати остаточне зупинення військової агресії в Україні. The aggravation of the global problems of humanity’s existence has led to a rapid and radical change in value orientations and strategic priorities for the further development of world economies. The concepts of socio-ecological and economic justice, equality, and access to financial benefits have replaced and supplemented the dominant commercial business management concepts. The idea of inclusive development has become one of the main ones among such concepts. Its principles aim to overcome gaps and inequalities in the population’s quality of life. The agricultural sector plays a decisive role in this. The article investigates the inclusive agricultural business’s key priorities, characteristics, and principles. A review of literary sources was carried out devoted to the issue of inclusiveness in the development of agriculture and rural areas. The author’s variation supplemented the fundamental principles of inclusive agrarian business. The landscape of the main tasks of using the resource potential of agribusiness under the conditions of an inclusive rural economy is determined. An analysis of the state, volumes, and value of the resource potential of agribusiness of Ukraine under pre-war conditions was carried out. The research results showed significant problems in the formation of the resource potential of the agricultural sector in terms of human resources, fixed assets, and intangible assets. Despite this, the results demonstrated the agrarian sector’s investment attractiveness and agribusiness’s high profitability. The thesis confirmed a significant potential for ensuring the future economic growth of the agricultural industry based on inclusive development. The critical strategic principle of managing the resource potential of inclusive farm businesses should be a compromise and an optimal combination of commercial business initiatives with a high level of social responsibility for agricultural producers. The final cessation of the military conflict on the territory of Ukraine should become a mandatory prerequisite for realizing this goal. The prospects for further scientific research in this context are the assessment of the dependence of the effectiveness of the use of the resource potential of agricultural business entities depending on the degree of implementation of the inclusive principles of its development in practical activities.
Use and reproduction of the resource potential of agricultural business under the conditions of an inclusive economy
Keywords: сільське господарство; агропотенціал; сталий розвиток; сільські території; агроекономіка; agriculture; agricultural potential; sustainable development; rural areas; agricultural economy